Social entrepreneurship in hospitality : principles and strategies for change /: principles and strategies for change. (2020) - Legrand, Willy; Gardetti, Miguel Ángel; Nielsen, Robert Schønrock; Johnson, Colin; Ergül, Mehmet
No abstract available